Characterization of heterologously expressed Fibril, a shape and motility determining cytoskeletal protein of the helical bacterium Spiroplasma - Shrikant Harne; Pananghat Gayathri (iScience, 2022)
Summary: Fibril is a constitutive filament-forming cytoskeletal protein of unidentified fold, exclusive to members of genus Spiroplasma. It is hypothesized to undergo conformational changes necessary to bring about Spiroplasma motility through changes in cell helicity. However, the mechanism driving conformational changes in Fibril remains unknown. We expressed Fibril from S. citri in E. coli for its purification and characterization. Sodium dodecyl sulfate solubilized Fibril filaments and facilitated purification by affinity chromatography. An alternative protocol for obtaining enriched insoluble Fibril filaments was standardized using density gradient centrifugation. Electron microscopy of Fibril purified by these protocols revealed filament bundles. Probable domain boundaries of Fibril protein were identified based on mass spectrometric analysis of proteolytic fragments. Presence of α-helical and β-sheet signatures in FT-IR measurements suggests that Fibril filaments consist of an assembly of folded globular domains, and not a β-strand-based aggregation like amyloid fibrils.